The effect of highly competitive exercises on developing the kinematic speed of the hip rotation and the Kochi grab - Gary - Ogi - Mata for young judo players - Yaqoob , Liza Rustum (International Journal of Psychosocial Rehabilitation, 2020)
The exercises are very competitive in the sports training process, which pertains to the judo wrestling game, which is one of the best combat competitive sports and works on developing comprehensive physical fitness, as the players ’movement in the competition requires a high physical exertion and what requires it to endure the extreme physical exertion and the burden on their physical capabilities. The research problem lies in the presence of a clear weakness in the kinetic speed of the hip rotation despite the critical importance of obtaining an entire point or the largest number of parts of the point as well as is a defensive and offensive method against the opponent's movements to overcome it and the adoption of exercises with intense competition, which has a noticeable effect during performance and at the best level The aim of the research is to prepare numbers of highly competitive exercises in developing the kinematic speed of the hip rotation and the Kochi grab - current - augi - mata for young judo players and to identify the impact of the competition severity exercises in developing the kinetic speed of the hip rotation and the kochi grab - gi - oji - mata for young judo players. Research that strongly competitive exercises have a positive effect in developing the kinematic speed of the hip rotation and the Koachi-Gari-Ogi-Mata grab for young judo players. The researcher adopted the experimental approach with equal groups and determined the research community for young judo players by (12) players under the age of 20 years and weighing (66 kg), and they were prepared and adapted about the codified training program in terms of performance. Special exercises were applied to the two groups for eight weeks and with three training units per week. The researcher used the statistical bag SPSS, and the researcher reached the most important conclusions - that the intensity of the exercises had a positive impact on developing the kinematic speed of the hip rotation and Guchi-Gari-Ogi-Matta judo players Youth.